Ferulic acid composite material, applications thereof, and methods for producing ferulic acid composite material

JP2025032611APending Publication Date: 2025-03-12SEKISUI PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023137982
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-03-12

AI Technical Summary

Benefits of technology

【0009】 本発明の実施形態によれば、紫外線防御能に優れ且つアルコール耐性に優れたフェルラ酸複合材料を提供することができる。また、本発明の実施形態によれば、紫外線防御能に優れ且つアルコール耐性に優れたフェルラ酸複合材料の用途を提供することができる。さらに、本発明の実施形態によれば、紫外線防御能に優れ且つアルコール耐性に優れたフェルラ酸複合材料を製造する方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032611000001
    Figure 2025032611000001
Patent Text Reader

Abstract

To provide a ferulic acid composite material with superior ultraviolet shielding capability and superior alcohol resistance, applications of the ferulic acid composite material, and methods for producing the ferulic acid composite material.SOLUTION: A ferulic acid composite material according to an embodiment of the present invention comprises a substrate and a polyvalent metal salt of ferulic acid, wherein the substrate comprises at least one selected from the group consisting of organic substrates and inorganic substrates, and the polyvalent metal salt of ferulic acid is attached to at least a part of the surface of the substrate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferulic acid composite material, its uses, and a method for producing the ferulic acid composite material. [Background technology]

[0002] Ferulic acid is a phenolic compound that is widely present in plant cell walls. Ferulic acid has UV protection, antioxidant, and antibacterial properties, and is useful as a raw material for cosmetics, medicines, agricultural chemicals, food additives, etc. (Patent Document 1).

[0003] Recently, a technique has been proposed for imparting ultraviolet protection ability to pigment powders to be blended in cosmetics and the like by precipitating ferulic acid on the surface of the pigment powder using a specific surface treatment method (Patent Document 2). This surface treatment method has been reported as a method in which the pigment powder is mixed and dispersed in an aqueous solution in which ferulic acid is dissolved in water as a salt under basic conditions of pH = 9 to 14 with sodium hydroxide, and the aqueous solution is made acidic with pH = 1 to 5 with hydrochloric acid, thereby precipitating the ferulic acid on the surface of the pigment powder.

[0004] Materials such as pigment powders that are blended into cosmetics and the like may often have alcohol added during the manufacturing process or may be blended with alcohol at the productization stage.

[0005] Therefore, the present inventors performed alcohol cleaning on a substrate that had been surface-treated by the surface treatment method proposed in Patent Document 2. As a result, it was found that the UV protection ability of the substrate after alcohol cleaning was reduced compared to before cleaning. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2006-67803 A [Patent Document 2] JP 2018-162400 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made to solve the above-mentioned problems in the conventional art, and its main object is to provide a ferulic acid composite material having excellent UV protection ability and excellent alcohol resistance, to provide uses for such a ferulic acid composite material, and to provide a method for producing such a ferulic acid composite material. [Means for solving the problem]

[0008] [1] A ferulic acid composite material according to an embodiment of the present invention comprises a base material and a polyvalent metal salt of ferulic acid, the base material comprising at least one selected from the group consisting of organic base materials and inorganic base materials, and the polyvalent metal salt of ferulic acid is attached to at least a portion of the surface of the base material. [2] In the ferulic acid composite material described in [1] above, the organic base material may contain at least one selected from the group consisting of cellulose, starch, and crosslinked starch. [3] In the ferulic acid composite material described in [1] above, the inorganic base material may contain at least one selected from the group consisting of mica and sericite. [4] In the ferulic acid composite material described in any one of [1] to [3] above, the polyvalent metal salt may be a salt of at least one metal selected from the group consisting of aluminum, zinc, magnesium, calcium, titanium, and zirconium. [5] The ferulic acid composite material according to any one of [1] to [4] above may contain a surface treatment agent other than the polyvalent metal salt of ferulic acid. [6] An external preparation according to an embodiment of the present invention comprises a ferulic acid composite material described in any one of [1] to [5] above. [7] A method for producing a ferulic acid composite material according to an embodiment of the present invention is a method for producing a composite material in which a polyvalent metal salt of ferulic acid is attached to at least a portion of the surface of a substrate, comprising dissolving ferulic acid as a ferulate salt in basic water to prepare an aqueous solution of the ferulate salt, and mixing the aqueous solution with the substrate and a salt of at least one metal selected from the group consisting of aluminum, zinc, magnesium, calcium, titanium, and zirconium. Effect of the Invention

[0009] According to an embodiment of the present invention, a ferulic acid composite material having excellent UV protection ability and excellent alcohol resistance can be provided. Also, according to an embodiment of the present invention, a use of the ferulic acid composite material having excellent UV protection ability and excellent alcohol resistance can be provided. Furthermore, according to an embodiment of the present invention, a method for producing a ferulic acid composite material having excellent UV protection ability and excellent alcohol resistance can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0011] 1. Ferulic acid composite material A ferulic acid composite material according to an embodiment of the present invention includes a base material and a polyvalent metal salt of ferulic acid.

[0012] As long as the ferulic acid composite material according to an embodiment of the present invention contains a base material and a polyvalent metal salt of ferulic acid, it may contain any other appropriate components as long as the effects of the present invention are not impaired.

[0013] The total content of the base material and the polyvalent metal salt of ferulic acid in the ferulic acid composite material according to the embodiment of the present invention is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, particularly preferably 95% by weight to 100% by weight, and most preferably 99% by weight to 100% by weight.

[0014] In the ferulic acid composite material according to the embodiment of the present invention, a polyvalent metal salt of ferulic acid is attached to at least a part of the surface of a substrate. The term "attached" as used herein may mean a physical fixation, a chemical bond, or a combination thereof.

[0015] In the ferulic acid composite material according to an embodiment of the present invention, the amount of the polyvalent metal salt of ferulic acid attached to the surface of the substrate varies depending on the type, shape, and size of the substrate, and is, for example, 0.0001% by weight to 100% by weight relative to the substrate, and is preferably 0.001% by weight to 50% by weight, and more preferably 0.01% by weight to 30 parts by weight, in order to further exert the effects of the present invention.

[0016] The substrate includes at least one selected from the group consisting of organic substrates and inorganic substrates.

[0017] As the organic substrate, any suitable organic substrate may be adopted as long as it does not impair the effects of the present invention. The organic substrate may be one type or two or more types. Examples of such organic substrates include cellulose, starch, crosslinked starch, silk powder, and resin powder. In terms of being able to further exhibit the effects of the present invention, the organic substrate preferably includes at least one selected from the group consisting of cellulose, starch, and crosslinked starch, and more preferably at least one selected from the group consisting of cellulose, starch, and crosslinked starch. Examples of crosslinked starch include phosphate crosslinked starch, acetylated adipic acid crosslinked starch, acetylated phosphate crosslinked starch, hydroxypropylated phosphate crosslinked starch, and phosphate monoesterified phosphate crosslinked starch.

[0018] As the inorganic substrate, any suitable inorganic substrate may be adopted as long as the effect of the present invention is not impaired. The inorganic substrate may be one type or two or more types. Examples of such inorganic substrates include mica, sericite, hydroxyapatite, vermiculite, higilite, bentonite, montmorillonite, hectorite, zeolite, ceramic powder, titanium oxide, zirconium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, talc, kaolin, silicic acid, silicic anhydride, aluminum silicate, magnesium silicate, aluminum magnesium silicate, calcium silicate, barium silicate, strontium silicate, metal tungstate, secondary calcium phosphate, alumina, aluminum hydroxide, boron nitride, boron nitride, and silica. In terms of being able to further exert the effects of the present invention, the inorganic substrate preferably contains at least one selected from the group consisting of mica and sericite, and more preferably is at least one selected from the group consisting of mica and sericite.

[0019] The ferulic acid composite material according to the embodiment of the present invention contains a polyvalent metal salt of ferulic acid. The ferulic acid composite material according to the embodiment of the present invention contains ferulic acid in the form of a polyvalent metal salt, and thus can have excellent ultraviolet protection ability and excellent alcohol resistance. As described above, when a composite material having conventional ferulic acid attached to the surface of a substrate was washed with alcohol, it was found that the ultraviolet protection ability of the composite material after the alcohol washing was reduced compared to before the washing. Then, the inventors of the present invention have repeatedly studied the cause of the decrease in ultraviolet protection ability, and have focused on the alcohol resistance of ferulic acid. As a result of further studies, it has been found that when ferulic acid is attached to a substrate in the form of a polyvalent metal salt, the alcohol resistance is improved, and excellent ultraviolet protection ability can be exhibited.

[0020] The polyvalent metal salt in the polyvalent metal salt of ferulic acid may be any suitable polyvalent metal salt within the scope of the present invention without impairing the effects of the present invention. The polyvalent metal may be one type or two or more types. Examples of such polyvalent metals include aluminum, zinc, magnesium, calcium, titanium, zirconium, chromium, copper, cobalt, strontium, barium, and iron. In terms of being able to further exert the effects of the present invention, the polyvalent metal salt in the polyvalent metal salt of ferulic acid is preferably a salt of at least one metal selected from the group consisting of aluminum, zinc, magnesium, calcium, titanium, and zirconium, and more preferably aluminum.

[0021] The ferulic acid composite material according to the embodiment of the present invention may contain an ultraviolet absorber other than the polyvalent metal salt of ferulic acid. The ultraviolet absorber may be only one type, or may be two or more types. Any appropriate ultraviolet absorber may be adopted as such an ultraviolet absorber as long as it does not impair the effects of the present invention. As such an ultraviolet absorber, a water-soluble ultraviolet absorber is preferable, and a water-soluble acidic ultraviolet absorber is more preferable. The content ratio of the ultraviolet absorber other than the polyvalent metal salt of ferulic acid in the ferulic acid composite material according to the embodiment of the present invention is preferably 50% by weight or less, more preferably 30% by weight or less, even more preferably 10% by weight or less, particularly preferably 5% by weight or less, and most preferably 1% by weight or less.

[0022] The ferulic acid composite material according to the embodiment of the present invention may contain a surface treatment agent other than the polyvalent metal salt of ferulic acid. The surface treatment agent may be one type or two or more types. Any appropriate surface treatment agent may be adopted as the surface treatment agent as long as it does not impair the effects of the present invention. Examples of such surface treatment agents include silicone compounds, silane coupling agents, metal soap-based treatment agents, amino acid-based treatment agents, phospholipid-based treatment agents, glycolipid-based treatment agents, complex lipid-based treatment agents, and ceramide-based treatment agents, and preferably silane coupling agents and metal soap-based treatment agents. The content ratio of the surface treatment agent other than the polyvalent metal salt of ferulic acid in the ferulic acid composite material according to the embodiment of the present invention is preferably 50% by weight or less, more preferably 30% by weight or less, even more preferably 10% by weight or less, particularly preferably 5% by weight or less, and most preferably 1% by weight or less.

[0023] The ferulic acid composite material according to the embodiment of the present invention can have improved water resistance when a metal soap-based treatment is used as a surface treatment agent. Examples of metal soap-based treatment agents include metal stearates, metal palmitates, metal myristates, metal laurates, metal caprates, metal caprylates, metal behenates, metal oleates, metal cetyl phosphates, and metal 12-hydroxystearates. Examples of metals in the metal salts of such metal soap-based treatment agents include zinc, aluminum, calcium, and magnesium.

[0024] The ferulic acid composite material according to the embodiment of the present invention has an ultraviolet light reflectance (II) at 375 nm, when the reflectance value of a barium sulfate white plate is taken as 100%, of preferably 75% or less, more preferably 60% or less, even more preferably 50% or less, particularly preferably 40% or less, and most preferably 30% or less. The lower limit of the ultraviolet light reflectance is 0%.

[0025] In the ferulic acid composite material according to the embodiment of the present invention, the difference ((I)-(II)) between the ultraviolet light reflectance (I) of the substrate material and the ultraviolet light reflectance (II) of the resulting ferulic acid composite material at 375 nm, when the reflectance value of a barium sulfate white plate is taken as 100%, is preferably 15% or more, more preferably 30% or more, even more preferably 40% or more, particularly preferably 50% or more, and most preferably 60% or more. The upper limit of the difference ((I)-(II)) is 100%.

[0026] 2. Manufacturing method of ferulic acid composite material The ferulic acid composite material according to the embodiment of the present invention can be produced by any suitable method as long as the effect of the present invention is not impaired. In terms of being able to more effectively exhibit the effect of the present invention, the method for producing the ferulic acid composite material according to the embodiment of the present invention is typically a method for producing a composite material in which a polyvalent metal salt of ferulic acid is attached to at least a part of the surface of a substrate, in which ferulic acid is dissolved as a ferulic acid salt in a basic aqueous solution to prepare an aqueous solution of the ferulic acid salt, and the aqueous solution is mixed with the substrate and at least one salt of a metal selected from the group consisting of aluminum, zinc, magnesium, calcium, titanium, and zirconium.

[0027] In the method for producing a ferulic acid composite material according to an embodiment of the present invention, the aqueous solution of a ferulate salt is typically prepared by dissolving ferulic acid as a ferulate salt in a basic aqueous solution.

[0028] The amount of the basic aqueous solution used relative to ferulic acid may be any appropriate amount within the range that does not impair the effects of the present invention. The amount of the basic aqueous solution used is, for example, 1.0 to 10 parts by weight relative to 1 part by weight of ferulic acid, and is preferably 2.0 to 9.0 parts by weight, more preferably 3.0 to 8.0 parts by weight, and even more preferably 4.0 to 7.0 parts by weight in terms of further exerting the effects of the present invention.

[0029] The pH of the basic aqueous solution is typically pH=8-12, and preferably pH=8-11.

[0030] The type of base for preparing the basic aqueous solution includes, for example, inorganic bases and organic bases.

[0031] Examples of the inorganic base include sodium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium hydroxide, potassium carbonate, and potassium hydrogen carbonate.

[0032] The organic base includes, for example, ammonia, triethylamine, and triethanolamine.

[0033] As for the base material, the explanation in the section <<1. Ferulic acid composite material>> can be used.

[0034] The amount of the base material used may be any appropriate amount within the range that does not impair the effects of the present invention. The amount of the base material used is, for example, 1 part by weight to 10,000 parts by weight relative to 1 part by weight of ferulic acid, and from the viewpoint of further exerting the effects of the present invention, is preferably 2 parts by weight to 1,000 parts by weight, more preferably 3 parts by weight to 500 parts by weight, particularly preferably 4 parts by weight to 100 parts by weight, and most preferably 5 parts by weight to 50 parts by weight.

[0035] Examples of the salt of at least one metal selected from the group consisting of aluminum, zinc, magnesium, calcium, titanium, and zirconium include aluminum salts such as aluminum chloride, polyaluminum chloride, aluminum sulfate, aluminum nitrate, potassium aluminum bisulfate, sodium aluminum bisulfate, potassium alum, ammonium alum, sodium alum, and sodium aluminate; zinc salts such as zinc chloride, zinc sulfate, and zinc nitrate; magnesium salts such as magnesium chloride, magnesium sulfate, and magnesium nitrate; calcium salts such as calcium chloride and calcium nitrate; titanium salts such as titanium chloride and titanium sulfate; and zirconium salts such as zirconium chloride, zirconium sulfate, and zirconium nitrate. Among these, aluminum salts are preferred, and aluminum sulfate is more preferred, in that they can more effectively express the effects of the present invention.

[0036] The amount of polyvalent metal used is, for example, 0.1 to 5.0 parts by weight per part by weight of ferulic acid, and in terms of further exerting the effects of the present invention, is preferably 0.2 to 4.0 parts by weight, more preferably 0.3 to 3.0 parts by weight, particularly preferably 0.4 to 2.0 parts by weight, and most preferably 0.5 to 1.5 parts by weight.

[0037] 3. Uses of ferulic acid composite material The ferulic acid composite material according to the embodiment of the present invention has excellent UV protection ability and excellent alcohol resistance, and therefore can be applied to various applications, and can be particularly suitably used as an external preparation.

[0038] The topical preparation according to the embodiment of the present invention includes the ferulic acid composite material according to the embodiment of the present invention. Any appropriate topical preparation may be selected as the topical preparation as long as it does not impair the effects of the present invention. Examples of such topical preparations include basic cosmetics such as milky lotion, cream, lotion, essence, gel, pack, and face wash; makeup cosmetics such as lipstick, makeup base, foundation, and makeup pressed powder; cleansing cosmetics such as face wash, body shampoo, and soap; bath additives; and sunscreen cosmetics. Among these, the ferulic acid composite material according to the embodiment of the present invention has excellent ultraviolet protection ability and excellent alcohol resistance, and therefore can be particularly suitably used in sunscreen cosmetics.

[0039] The content ratio of the ferulic acid composite material according to the embodiment of the present invention in the topical preparation according to the embodiment of the present invention can be appropriately set according to the purpose within a range that does not impair the effects of the present invention. The content ratio of the ferulic acid composite material according to the embodiment of the present invention in the topical preparation according to the embodiment of the present invention is, for example, 0.0001% by weight to 100% by weight, preferably 0.001% by weight to 100% by weight, more preferably 0.01% by weight to 100% by weight, even more preferably 0.1% by weight to 100% by weight, and particularly preferably 1% by weight to 100% by weight, based on the total amount of the topical preparation.

[0040] The topical preparation according to the embodiment of the present invention may contain any suitable component that is usually used in topical preparations, in addition to the ferulic acid composite material according to the embodiment of the present invention. Such components include, for example, oils, pigments, dyes, fluorine compounds, resins, surfactants, thickeners, waxes, preservatives, fragrances, moisturizers, salts, solvents, antioxidants, chelating agents, neutralizing agents, pH adjusters, and cosmetic ingredients (skin whitening agents, cell activators, anti-inflammatory agents, blood circulation promoters, skin astringents, antiseborrheic agents, etc.). EXAMPLES

[0041] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".

[0042] <Evaluation of UV protection ability> A UV-Vis-Near-Infrared Spectrophotometer (Shimadzu Corporation, product name "UV-3600Plus") was used as a measuring device for UV reflectance, and a 60 mm Φ integrating sphere was used to fill a powder sample holder with a substrate or composite material to obtain a sample. The reflection characteristics of the obtained sample in the UV region (wavelength 200 nm to 400 nm) were measured as UV reflectance (%). The inner surface of the integrating sphere was painted with barium sulfate. For the measurement, the reflectance value of a white board of barium sulfate was set as 100%, and the UV reflectance (I) of the substrate used at 375 nm and the UV reflectance (II) of the obtained composite material at 375 nm were measured for each of the examples and comparative examples. In addition, the difference between the ultraviolet reflectance (I) and the ultraviolet reflectance (II), (I)-(II), was calculated. The smaller the ultraviolet reflectance (II) value, the higher the ultraviolet protection ability of the obtained composite material. In addition, the greater the difference (I)-(II) between the ultraviolet reflectance (I) and the ultraviolet reflectance (II), the greater the improvement in ultraviolet protection ability due to the addition of the polyvalent metal salt of ferulic acid, when the ultraviolet protection ability inherent to the base material is used as the standard.

[0043] <Evaluation of alcohol resistance> Alcohol resistance was evaluated by measuring the UV reflectance before and after ethanol washing. Specifically, the evaluation was performed as follows. 1.0 g of the measurement object and 5.0 g of ethanol were placed in a plastic centrifuge tube, and the operations of dispersion, centrifugation, and removal of the supernatant were repeated three times. The UV reflectance of the measurement object at 375 nm before and after ethanol washing was measured, and the rate of change (rate of change (%) = [(UV reflectance after ethanol washing (%) - UV reflectance before ethanol washing (%)) / UV reflectance before ethanol washing (%)] × 100) was calculated and used as an index of alcohol resistance.

[0044] <Water resistance evaluation> Approximately 0.1 g of the measurement target was weighed out and applied evenly to an artificial skin (manufactured by Beaulax, product name "Bio Skin Plate") with a finger. Approximately 0.02 g of ion-exchanged water was then dropped onto the applied surface of the measurement target with a dropper, and the state of the water droplets was observed after 10 seconds. When the water did not penetrate and the droplet shape was maintained, it was evaluated as ◯, and when the water penetrated slightly and the droplet shape was slightly distorted, it was evaluated as △.

[0045] [Production Example 1] A container was charged with 121 parts by weight of ion-exchanged water, 35 parts by weight of sodium chloride (manufactured by Ako Kasei Co., Ltd., product name "Mishio"), and 1.2 parts by weight of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product name "Sodium Hydroxide"), and the mixture was stirred at room temperature to dissolve the ingredients, producing an aqueous solution. 100 parts by weight of rice starch (manufactured by Joetsu Starch Co., Ltd., product name "Fine Snow") was added to the aqueous solution, and the mixture was stirred and dispersed at room temperature using a stirring blade at a rotation speed of 425 rpm, producing a rice starch dispersion. In the prepared dispersion, 5 parts by weight of sodium trimetaphosphate (manufactured by Yoneyama Chemical Industry Co., Ltd., product name "Sodium Trimetaphosphate") as a phosphate compound and 0.54 parts by weight of alkaline protease (manufactured by HIV Co., Ltd.) were added and dissolved by stirring at room temperature. Next, the mixture was reacted for 18 hours while maintaining the temperature at 40°C using a stirrer. After 18 hours, hydrochloric acid (manufactured by Fujifilm Wako Pure Chemical Industries, product name "20% hydrochloric acid") was added to the obtained dispersion of processed starch to neutralize it, and the neutralized dispersion was put into a pressure filtration device (manufactured by Advantec Co., Ltd., product name "KST-293-16-UH") and pressure filtered. After pressure filtration, the mixture was washed with ion-exchanged water and further dehydrated to obtain a powder. The obtained powder was dried at 80°C for 24 hours using a vacuum constant temperature dryer (manufactured by Yamato Scientific Co., Ltd., product name "DP43") to obtain a phosphate cross-linked starch.

[0046] [Example 1] 0.2 g of ferulic acid (Tsukuno Rice Fine Chemicals Co., Ltd.) was added to 20 g of ion-exchanged water, and the mixture was stirred and suspended for 30 minutes. Next, 1 g of 5% aqueous sodium hydroxide solution was added dropwise to adjust the pH to 12. It was confirmed that the suspension became completely transparent, and a yellow transparent aqueous sodium ferulate solution was obtained. 2 g of the phosphate cross-linked starch obtained in Production Example 1 was added thereto, and after dispersing for 10 minutes, 1 g of a 20% aqueous aluminum sulfate solution was added to precipitate aluminum ferulate on the surface of the phosphate cross-linked starch. Then, the mixture was filtered, dried, and pulverized to obtain a phosphate cross-linked starch surface-treated with aluminum ferulate as a composite material (1). The results are shown in Table 1.

[0047] [Example 2] Starch surface-treated with aluminum ferulate was obtained as composite material (2) in the same manner as in Example 1, except that the phosphate cross-linked starch was changed to rice starch (manufactured by Joetsu Starch Co., Ltd., product name "Fine Snow"). The results are shown in Table 1.

[0048] [Example 3] Cellulose surface-treated with aluminum ferulate was obtained as composite material (3) in the same manner as in Example 1, except that the phosphate cross-linked starch was changed to cellulose (manufactured by Fushimi Pharmaceutical Co., Ltd., product name "Compressel S"). The results are shown in Table 1.

[0049] [Example 4] Mica flakes surface-treated with aluminum ferulate were obtained as composite material (4) in the same manner as in Example 1, except that the phosphate cross-linked starch was changed to mica flakes (manufactured by Yamaguchi Mica Co., Ltd., product name "Y-1800"). The results are shown in Table 1.

[0050] [Example 5] Sericite surface-treated with aluminum ferulate was obtained as a composite material (5) in the same manner as in Example 1, except that sericite was used instead of phosphate-crosslinked starch. The results are shown in Table 1.

[0051] [Example 6] A phosphate-crosslinked starch surface-treated with zinc ferulate was obtained as a composite material (6) in the same manner as in Example 1, except that the 20% aqueous solution of aluminum sulfate was changed to a 10% aqueous solution of zinc chloride and the amount of the aqueous solution added was changed to 2.0 g. The results are shown in Table 1.

[0052] [Example 7] A phosphate-crosslinked starch surface-treated with calcium ferulate was obtained as a composite material (7) in the same manner as in Example 1, except that the 20% aqueous aluminum sulfate solution was changed to a 20% aqueous calcium chloride solution. The results are shown in Table 1.

[0053] [Example 8] A phosphate cross-linked starch surface-treated with magnesium ferulate was obtained as a composite material (8) in the same manner as in Example 1, except that the 20% aqueous aluminum sulfate solution was changed to a 20% aqueous magnesium chloride solution. The results are shown in Table 1.

[0054] [Example 9] A mica piece surface-treated with aluminum ferulate and sodium myristate was obtained as a composite material (9) in the same manner as in Example 4, except that a mixture of 0.1 g of ferulic acid (manufactured by Tsuno Rice Fine Chemicals Co., Ltd.) and 0.10 g of sodium myristate was used instead of 0.2 g of ferulic acid (manufactured by Tsuno Rice Fine Chemicals Co., Ltd.). The results are shown in Table 1.

[0055] [Comparative Example 1] 0.2 g of ferulic acid (Tsukuno Rice Fine Chemicals) was added to 20 g of ion-exchanged water, and the mixture was stirred and suspended for 30 minutes. Next, 1 g of 5% aqueous sodium hydroxide solution was added dropwise to adjust the pH to 12. It was confirmed that the suspension became completely transparent, and a yellow-transparent aqueous sodium ferulate solution was obtained. 2 g of the phosphate cross-linked starch obtained in Production Example 1 was added thereto, and the suspension was dispersed for 10 minutes. Then, 5% hydrochloric acid was added until the pH reached 3, and ferulic acid was precipitated on the surface of the phosphate cross-linked starch. The mixture was then filtered, dried, and pulverized to obtain a phosphate cross-linked starch surface-treated with ferulic acid as a composite material (C1). The results are shown in Table 1.

[0056] [Comparative Example 2] Rice starch surface-treated with ferulic acid was obtained as a composite material (C2) in the same manner as in Comparative Example 1, except that the phosphate cross-linked starch was changed to rice starch (manufactured by Joetsu Starch Co., Ltd., product name "Fine Snow"). The results are shown in Table 1.

[0057] [Comparative Example 3] Cellulose surface-treated with ferulic acid was obtained as a composite material (C3) in the same manner as in Comparative Example 1, except that the phosphate cross-linked starch was changed to cellulose (manufactured by Fushimi Pharmaceutical Co., Ltd., product name "Compressel S"). The results are shown in Table 1.

[0058] [Comparative Example 4] Mica flakes surface-treated with ferulic acid were obtained as a composite material (C4) in the same manner as in Comparative Example 1, except that the phosphate cross-linked starch was changed to mica flakes (manufactured by Yamaguchi Mica Co., Ltd., product name "Y-1800"). The results are shown in Table 1.

[0059] [Comparative Example 5] Sericite surface-treated with ferulic acid was obtained as a composite material (C5) in the same manner as in Comparative Example 1, except that the phosphate cross-linked starch was changed to sericite. The results are shown in Table 1.

[0060] [Table 1] [Industrial Applicability]

[0061] The ferulic acid composite material according to the embodiment of the present invention has excellent UV protection ability and excellent alcohol resistance, and therefore can be applied to various applications, and can be particularly suitably used as an external preparation.

Claims

1. The present invention relates to a composition comprising a base material and a polyvalent metal salt of ferulic acid, The substrate includes at least one selected from the group consisting of organic substrates and inorganic substrates; The polyvalent metal salt of ferulic acid is attached to at least a portion of the surface of the substrate. Ferulic Acid Complex.

2. The ferulic acid composite material of claim 1 , wherein the organic base material comprises at least one selected from the group consisting of cellulose, starch, and crosslinked starch.

3. The ferulic acid composite material according to claim 1 , wherein the inorganic substrate comprises at least one selected from the group consisting of mica and sericite.

4. The ferulic acid composite material according to claim 1, wherein the polyvalent metal salt is a salt of at least one metal selected from the group consisting of aluminum, zinc, magnesium, calcium, titanium, and zirconium.

5. The ferulic acid composite material according to claim 1 , further comprising a surface treatment agent other than the polyvalent metal salt of ferulic acid.

6. An external preparation comprising the ferulic acid complex material according to any one of claims 1 to 5.

7. A method for producing a ferulic acid composite material in which a polyvalent metal salt of ferulic acid is attached to at least a portion of a surface of a substrate, comprising the steps of: ferulic acid is dissolved as a ferulate in basic water to prepare an aqueous solution of the ferulate; mixing the aqueous solution with a base material and a salt of at least one metal selected from the group consisting of aluminum, zinc, magnesium, calcium, titanium, and zirconium; Method for producing ferulic acid composite material.

Citation Information

Patent Citations

  • Method for producing ferulic acid

    JP2006067803A

  • Pigment powder surface treatment method

    JP2018162400A